Universal aging characteristics of macroscopically and microscopically dissimilar metallic glasses. (15th August 2018) - Wong, Kaikin; Krishnan, Rithin P.; Dufresne, Eric M.; Ohara, Koji; Sandy, Alec R.; Chathoth, Suresh M.
Abstract: Supercooled liquids and glasses, due to their intrinsically unstable nature, are known to relax continuously until an equilibrium state is reached. By exploring atomic relaxation, aging and microscopic structure of chemically similar but physically dissimilar metallic glasses, we find that neither the relaxation time nor aging correlate with the free volume or density of the glasses. Furthermore, atomic relaxation time in these metallic glasses does not depend on the microscopic structure of the systems. The activation energy for the diffusion process indicates a completely different microscopic mechanism governing the atomic transport process. Nevertheless, the age-dependent relaxation time surprisingly exhibits a universal time-waiting time-temperature superposition. Our results provide a convincing proof of the universality in the aging of out-of-equilibrium materials. Graphical abstract: Image 1